Methadone inhibits CYP2D6 and UGT2B7/2B4 in vivo: a study using codeine in methadone‐ and buprenorphine‐maintained subjects - Gelston, Eloise A.; Coller, Janet K.; Lopatko, Olga V.; James, Heather M.; Schmidt, Helmut; White, Jason M.; Somogyi, Andrew A. (British journal of clinical pharmacology, 2012)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Although not well recognized, methadone inhibits CYP2D6 in vivo and in vitro and UGT2B7 and 2B4 in vitro. • We aimed to investigate the effect of methadone on the pathways of codeine metabolism, namely O‐demethylation (CYP2D6), 6‐glucuronidation (UGT2B4/7) and N‐demethylation (CYP3A4/2C8), in subjects maintained on methadone or buprenorphine as a control. WHAT THIS STUDY ADDS • Compared with subjects on buprenorphine, methadone reduced the clearance of codeine to morphine and to codeine‐6‐glucuronide but had no effect on norcodeine formation. • Plasma morphine concentrations remained unchanged, as although its formation was reduced, its metabolism to M3G and M6G was also reduced. • Metabolic drug interactions with methadone cannot assume substrate‐dependent inhibition. AIMS To compare the O‐demethylation (CYP2D6‐mediated), N‐demethylation (CYP3A4‐mediated) and 6‐glucuronidation (UGT2B4/7‐mediated) metabolism of codeine between methadone‐ and buprenorphine‐maintained CYP2D6 extensive metabolizer subjects. METHODS Ten methadone‐ and eight buprenorphine‐maintained subjects received a single 60 mg dose of codeine phosphate. Blood was collected at 3 h and urine over 6 h and assayed for codeine, norcodeine, morphine, morphine‐3‐ and ‐6‐glucuronides and codeine‐6‐glucuronide. RESULTS The urinary metabolic ratio for O‐demethylation was significantly higher (P= 0.0044) in the subjects taking methadone (mean ± SD, 2.8 ± 3.1) compared with those taking buprenorphine (0.60 ± 0.43), likewise for 6‐glucuronide formation (0.31 ± 0.24 vs. 0.053 ± 0.027; P < 0.0002), but there was no significant difference (P= 0.36) in N‐demethylation. Similar changes in plasma metabolic ratios were also found. In plasma, compared with those maintained on buprenorphine, the methadone‐maintained subjects had increased codeine and norcodeine concentrations (P < 0.004), similar morphine (P= 0.72) and lower morphine‐3‐ and ‐6‐ and codeine‐6‐glucuronide concentrations (P < 0.008). CONCLUSION Methadone is associated with inhibition of CYP2D6 and UGTs 2B4 and 2B7 reactions in vivo, even though it is not a substrate for these enzymes. Plasma morphine was not altered, owing to the opposing effects of inhibition of both formation and elimination; however, morphine‐6‐glucuronide (analgesically active) concentrations were substantially reduced. Drug interactions with methadone are likely to include drugs metabolized by various UGTs and CYP2D6.